Book Review: Amartya Sen, The Country of First Boys and Other Essays. (March 2016) - Sengupta, Amit
Amartya Sen, The Country of First Boys and Other Essays, New Delhi, The Little Magazine and Oxford University Press, 2015, 328 pp., ₹ 550, ISBN: 978-0-19-873818-3.